Reducing food loss and waste as a climate change mitigation strategy - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Welcome and overview of meeting on: Reducing food loss and waste as a climate change mitigation strategy November 14, 2018 Hosted by CCAFS Low Emissions Development as part of its Learning Platform on Low Emission Options